Concurrent Varicella with Herpes Zoster in A Child - Chowdhry, Sundeep; Jaiswal, Prashansa; Dhali, Tapan Kumar; Shukla, Akhilesh (Journal of Universal College of Medical Sciences, 2018)
A 3 year old girl presented with a two- day history of multiple fluid filled lesions on buttocks and back of left thigh. As informed by the child's mother, she had fever 4 days back and was irritable with pain and discomfort on back of the left thigh. The pain was episodic and radiated from buttocks to the leg. On examination, multiple fluid filled lesions of various sizes with surrounding erythema were present involving the S1, S2, S3 dermatomes extending from buttock to the sole sparing few areas in between the vesicles. On further examination of whole body, there were multiple discrete fluid filled lesions on erythematous base ranging from 0.1 to 0.3 mm diameter in size on chest, abdomen and back. Multinucleated giant cells with acantholytic cells were found in Tzank smears. Diagnosis of concurrent varicella with herpes zoster was made. Journal of Universal College of Medical Sciences (2016) Vol.04 No.01 Issue 13, Page: 38-40